Multi-Way Relaying Techniques for Heterogeneous Cooperative Wireless Network: From Theory to Practice - Wei Chen; Ke Ke; Yanping Yang; Ou Li (Dianxin kexue)
A heterogeneous network integration scheme based on cooperative relay technology was proposed, then the foundation of heterogeneous network was conceived through the relay node, with the aim to solve the transmission bottleneck between heterogeneous wireless access network by using the multidirectional relay technology, with the aid of cooperative communication. More specifically, based on WLAN and cellular networks, the effective integration and key technologies of the scene problems were investigated, then some possible solutions, with the purpose of meeting the indoor high data rate requirements and the outdoor high mobility requirements, so as to cost-effectively improve the quality of the user experience, were put forward.